Theorizing Slum Tourism: Performing, Negotiating and Transforming Inequality - Dürr, Eveline; Jaffe, Rivke (European Review of Latin American and Caribbean Studies, 2012)
Abstract:This Exploration focuses on the emerging field of slum tourism research, which has the potential to connect Latin American and Caribbean studies on tourism and urban inequality. Slum tourism involves transforming poverty, squalor and violence into a tourism product. Drawing on both altruism and voyeurism, this form of tourism is a complex phenomenon that raises various questions concerning power, inequality and subjectivity. This essay seeks to advance the theoretical debate on slum tourism research and to stimulate comparative studies. Introducing brief examples of slum tourism in Mexico and Jamaica, this contribution moves towards an initial theorization of the performance, negotiation and transformation of inequality in a framework of tourism and global mobilities.Resumen: Teorizar el Turismo en las zonas marginadas: Construcción, negociación y transformación de la desigualdadEsta Exploración se centra en el campo emergente del turismo en zonas marginadas, que tiene como potencial conectar a América Latina y el Caribe en los estudios sobre el turismo y la desigualdad urbana. Turismo 'Slum' implica la transformación de la pobreza, la miseria y la violencia en un producto turístico. Basándose tanto en el altruismo como en el voyerismo, esta forma de turismo es un fenómeno complejo que plantea diversas cuestiones relativas al poder, la desigualdad y la subjetividad. Con este ensayo se pretende avanzar en el debate teórico sobre la investigación de turismo en zonas marginadas y estimular estudios comparativos. Presentando ejemplos breves de turismo en barrios pobres en la ciudad de México y de Jamaica, esta contribución se mueve hacia una teorización inicial de la construcción, la negociación y la transformación de la desigualdad en el marco del turismo y la movilidad global.